Treatment of patients with prolonged course of medial temporal epilepsy - V. E. Kitaeva; A. S. Kotov (Эпилепсия и пароксизмальные состояния, 2018)
Objective. The aim of the study was to evaluate the efficacy of treatment in patients with prolonged duration of medial temporal epilepsy (MTE).Materials and methods. We studied cases of 93 patients with history of MTE lasted more than 10 years.Results. This form of epilepsy is often characterized by drug resistance; therefore, patients have to try different medications before the effective one is found (in 12% of cases, patients tried 5-7 different medicines). Nevertheless, in 48.4% of patients, pharmacotherapy is ineffective. According to our findings, patients with an early MTE debut and those with an epileptogenic focus (by EEG / MRI data) in the medial temporal zone are most likely to have treatment-resistant epilepsy.Conclusion. If the therapy is ineffective, patients should be referred to preoperational examination.